Effect of player role and competition level on player demands in basketball - Palmer, J.; Wundersitz, D.; Bini, R.; Kingsley, M. (Sports, 2021)
This study compared basketball training and match demands between player roles (starters, in-rotation bench players, out-rotation bench players) and between competition levels (semi-professional, professional). Thirty-seven players from one professional women`s team, one semi-professional women`s team, and one semi-professional men`s team wore accelerometers during training and matches throughout a competitive season. All teams were used for player role comparisons and the women`s teams were used to compare competition levels. Match and training session average intensity and volume, and durations of relative exercise intensities (inactive, light, moderate-vigorous, maximal, supramaximal) were calculated. Compared to out-rotation bench players, starters experienced twice the average match intensity and volume, spent 50% less match time being inactive, and spent 1.7-4.2× more match time in all other activity categories (p < 0.01). Compared to in-rotation bench players, starters experienced 1.2× greater average match intensity and volume, spent 17% less match time being inactive, and spent 1.4-1.5× more match time performing moderate-vigorous and maximal activity (p < 0.01). No differences in match demands were found between women`s competition levels, however the professional team experienced double the cumulative weekly training volume of the semi-professional team and spent 1.6-2.1× more cumulative weekly time in all activity categories (p < 0.01). To improve performance and reduce injury risk, players should prepare for the greatest match demands they could encounter during a season while considering potential changes to their role. Additionally, players might need their training volume managed when transitioning from a semi-professional to a professional season to reduce the injury risk from sharp increases in training demands.